Evaluación de pasivos ambientales puntuales sobre el recurso agua ocasionados por extractoras de aceite en el río Cucaracha, cantón La Concordia - Cevallos Macías, Anthony Ariel (2022)
The objective of this research was to assess the environmental liabilities in the Cucaracha River, caused by African palm oil extraction activities, for which an observation tour was carried out over the river, applying a form for the identification of environmental liabilities. For the valuation of the liabilities, a physicochemical analysis of the water was taken into account in which the parameters pH, Electrical Conductivity, Temperature, Total Suspended Solids, Total Dissolved Solids, Turbidity, Oils and Fats, Biochemical Oxygen Demand and Chemical Demand were evaluated. of Oxygen; Therefore, 2 samples were taken per passive, 100 meters (upstream) before the residual discharge from the oil extractors to the riverbed and the second at 100 meters (downstream) after the residual discharge in the water body. 3 environmental liabilities were identified corresponding to Unipal S.A., Teobroma and Molsando S.A. Associated with the same environmental aspect due to the filtration of oily spills from the extractors, its subsequent evaluation showed that the liabilities are in a moderate non-critical range, likewise the physicochemical results do not exceed the maximum permissible limits. Mitigation measures were proposed based on the identified environmental liabilities, establishing a strategy with a biological approach, which have a high percentage of efficiency and low cost.